New proposal to revise the classification for squamous cell carcinoma of the external auditory canal and middle ear. Issue 4 (31st March 2021) - Shinomiya, H; Uehara, N; Fujita, T; Yoshida, K; Imamura, Y; Teshima, M; Kimura, H; Miyawaki, D; Kakigi, A; Kiyota, N; Otsuki, N; Sasaki, R; et al.
Abstract: Background: The prognosis of patients with advanced squamous cell carcinoma of the external auditory canal and middle ear has been improved by advances in skull base surgery and multidrug chemoradiotherapy during the last two decades. Methods: Ninety-five patients with squamous cell carcinoma of the external auditory canal and middle ear who were treated between 1998 and 2017 were enrolled. The number of patients with tumour stages T1, T2, T3 and T4 was 15, 22, 24 and 34, respectively. Oncological outcomes and prognostic factors were retrospectively investigated. Results: Among patients with T4 disease, invasion of the brain ( p = 0.024), carotid artery ( p = 0.049) and/or jugular vein ( p = 0.040) were significant predictors of poor prognosis. The five-year overall survival rate of patients with at least one of these factors (T4b ) was significantly lower than that of patients without these factors (T4a ) (25.5 vs 65.5 per cent, p = 0.049). Conclusion: It is proposed that stage T4 be subclassified into T4a and T4b according to the prognostic factors.